Mechanisms of Phototoxic Effects of Cationic Porphyrins on Human Cells In Vitro - Yegor E. Yegorov; Khava S. Vishnyakova; Xiaowen Pan; Anton E. Egorov; Konstantin V. Popov; Liana L. Tevonyan; Galina V. Chashchina; Dmitry N. Kaluzhny (Molecules, 2023)
The toxic effects of four cationic porphyrins on various human cells were studied in vitro. It was found that, under dark conditions, porphyrins are almost nontoxic, while, under the action of light, the toxic effect was observed starting from nanomolar concentrations. At a concentration of 100 nM, porphyrins caused inhibition of metabolism in the MTT test in normal and cancer cells. Furthermore, low concentrations of porphyrins inhibited colony formation. The toxic effect was nonlinear; with increasing concentrations of various porphyrins, up to about 1 μM, the effect reached a plateau. In addition to the MTT test, this was repeated in experiments examining cell permeability to trypan blue, as well as survival after 24 h. The first visible manifestation of the toxic action of porphyrins is blebbing and swelling of cells. Against the background of this process, permeability to porphyrins and trypan blue appears. Subsequently, most cells (even mitotic cells) freeze in this swollen state for a long time (24 and even 48 h), remaining attached. Cellular morphology is mostly preserved. Thus, it is clear that the cells undergo mainly necrotic death. The hypothesis proposed is that the concentration dependence of membrane damage indicates a limited number of porphyrin targets on the membrane. These targets may be any ion channels, which should be considered in photodynamic therapy.